2022
DOI: 10.1177/10870547221092120
|View full text |Cite
|
Sign up to set email alerts
|

Is Parents’ ADHD Symptomatology Associated With the Clinical Feasibility or Effectiveness of a Psychoeducational Program Targeting Their Children’s ADHD?

Abstract: Objective: To examine if the clinical feasibility and effectiveness of a psychoeducational program targeting children’s ADHD differ between parents with varying ADHD symptom severities. Method: An open trial analyzed data from 549 parents of children with ADHD aged 3 to 17 years, who participated in psychoeducation at an outpatient habilitation/disability clinic. In all analyses, parents were stratified into three symptom severity groups (low/middle/high) based on scores on an ADHD screening scale. Results: Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…Seven studies involved community samples of parents ( 72 , 75 80 ). Three studies’ participants were parents of children with and without ADHD diagnosis ( 66 , 74 , 81 ) and five studies involved only parents of children with ADHD ( 68 , 71 , 73 , 82 , 83 ). Two studies reporting group comparisons ( 77 , 83 ) grouped community samples of parents according to varying levels of ADHD symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies involved community samples of parents ( 72 , 75 80 ). Three studies’ participants were parents of children with and without ADHD diagnosis ( 66 , 74 , 81 ) and five studies involved only parents of children with ADHD ( 68 , 71 , 73 , 82 , 83 ). Two studies reporting group comparisons ( 77 , 83 ) grouped community samples of parents according to varying levels of ADHD symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies examined changes in parental stress levels as a result of psychoeducation (Anderson & Guthery, 2015; Chacko et al, 2009; Ferrin et al, 2014; Ferrin et al, 2020; Gümüs et al, 2020; Lindström et al, 2022; Miller & Brooker, 2017; Nuri et al, 2022). Of these eight studies, six reported significant reductions in parental stress levels while the remaining studies showed no impact (Anderson & Guthery, 2015; Chacko et al, 2009; Gümüs et al, 2020; Lindström et al, 2022; Miller & Brooker, 2017; Nuri et al, 2022), five studies used a control group (Chacko et al, 2009; Ferrin et al, 2014; Ferrin et al, 2020; Gümüs et al, 2020; Nuri et al, 2022). The following instruments were used to measure the levels of parental stress: (1) PSI; (2) Parenthood Stress Questionnaire; (3) Perceived Stress Scale‐10; (4) Parental Stress Scale; (5) Caregiver Stress Scale and (6) Appraisal of Stress in Child Rearing (ASCR).…”
Section: Resultsmentioning
confidence: 99%
“…All three studies which measured parent knowledge showed improvement post‐treatment (Bai et al, 2015; Dixon et al, 2023; Lindström et al, 2022). However, most studies measured this using direct questioning and questionnaires including: (1) ADHD Beliefs and Attitudes Scale and (2) an investigator designed Likert‐style questionnaire, and only one study included a control group (Bai et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participant completion: participants attending at least 9 of the 12 (75%) sessions are considered to have completed the program [ 33 ].…”
Section: Methodsmentioning
confidence: 99%